POSITIVE INFLUENCE OF PT. PERTAMINA EP ASSETS 1 RANTAU FIELD TO INCREASING THE WELFARE OF SURROUNDING COMMUNITIES: IMPACT AND BENEFITS ANALYSIS - Nurul Mawaddah (International Journal of Educational Review, Law And Social Sciences (IJERLAS), 2021)
The purpose of this study was to assess how much influence the Corporate Social Responsibility (CSR) program of PT Pertamina EP Asset 1 Rantau Field has on improving the welfare of the community around the company. The research method used was quantitative method with descriptive statistical analysis, and data were analyzed using SPSS 26 software. Primary data was obtained by distributing questionnaires to the direct beneficiaries of the CSR program, 103 of the seven villages implementing the CSR program as well as the surrounding villages. The sample in this study used a census technique with a total of 103 respondents. Data analysis was carried out by validity test, reliability test, simple linear regression analysis, t test (partial), and coefficient of determination test (R2). The results showed that the Corporate Social Responsibility (CSR) program had a significant effect on increasing the welfare of the community around the company. This is evident from the results of the t test which shows a t value of 4.043 with a significance value of 0.000. In addition, based on the results of the test for the coefficient of determination or R Square, a value of 13.9% was obtained. Thus, it can be concluded that the CSR program contributes 13% to improving people's welfare, while the remaining 86.1% is influenced by other variables not explained in this study. Based on the research results, PT Pertamina EP Asset 1 Rantau Field should conduct a further evaluation further related to the community's needs so that the distribution of Corporate Social Responsibility (CSR) program assistance can be right on target, carried out in a sustainable and equitable manner so that it can help improve the welfare of society with a wider scope. This is expected to optimize the effectiveness of the CSR program and avoid plagiarism in presenting research results.